ANALISIS PENYERAPAN TENAGA KERJA DI KOTA KUPANG PROPINSI NUSA TENGGARA TIMUR TAHUN 2005 – 2010 - Tomasowa, Olivia Tomasowa Louise Eunike; Pudjihardjo, Muhammad (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2011)
The research is analyzing the absorption of workers at East Nusa Tenggara Province in period 2005-2010. Research aims at: identifying sectors with the strength of absorbing workers in period 2005-2010; understanding the output produced by sector workers at Kupang city; and acknowledging how is the effect of the economic growth on the absorption of workers at Kupang city in period 2005-2010. Analysis tools are Location Quotient (LQ), TK Productivity, TK Elasticity, MRP, and Klassen Typology. Result of research indicates that financial, building rent and company service sector, are superior sectors in absorbing workers.